Patterning of wound-induced intercellular Ca2+ flashes in a developing epithelium. (2nd September 2015) - Narciso, Cody; Wu, Qinfeng; Brodskiy, Pavel; Garston, George; Baker, Ruth; Fletcher, Alexander; Zartman, Jeremiah
Abstract: Differential mechanical force distributions are increasingly recognized to provide important feedback into the control of an organ's final size and shape. As a second messenger that integrates and relays mechanical information to the cell, calcium ions (Ca 2+ ) are a prime candidate for providing important information on both the overall mechanical state of the tissue and resulting behavior at the individual-cell level during development. Still, how the spatiotemporal properties of Ca 2+ transients reflect the underlying mechanical characteristics of tissues is still poorly understood. Here we use an established model system of an epithelial tissue, the Drosophila wing imaginal disc, to investigate how tissue properties impact the propagation of Ca 2+ transients induced by laser ablation. The resulting intercellular Ca 2+ flash is found to be mediated by inositol 1, 4, 5-trisphosphate and depends on gap junction communication. Further, we find that intercellular Ca 2+ transients show spatially non-uniform characteristics across the proximal–distal axis of the larval wing imaginal disc, which exhibit a gradient in cell size and anisotropy. A computational model of Ca 2+ transients is employed to identify the principle factors explaining the spatiotemporal patterning dynamics of intercellular Ca 2+ flashes. The relative Ca 2+ flash anisotropy is principally explained by local cell shape anisotropy. Further, Ca 2+ velocities are relatively uniform throughout the wing disc, irrespective of cell size or anisotropy. This can be explained by the opposing effects of cell diameter and cell elongation on intercellular Ca 2+ propagation. Thus, intercellular Ca 2+ transients follow lines of mechanical tension at velocities that are largely independent of tissue heterogeneity and reflect the mechanical state of the underlying tissue.